KUALITAS LATIHAN BERBASIS RESISTANCE TRAINING DALAM MENUNJANG PERFORMA FISIK DAN PENCEGAHAN CEDERA PADA ATLET MUDA: KAJIAN SPORT SCIENCE DI ASIOP FOOTBALL ACADEMY - Habain Sila Perdana; Samsul Arifin; Miftahudin Miftahudin (YLPK Mahardhika, 2026)
This study aims to evaluate the effectiveness of a structured resistance training program based on sport science principles in enhancing physical performance and reducing injury rates among youth athletes at ASIOP Football Academy. A quasi-experimental design with a pretest-posttest control group was employed, involving 40 athletes (aged 14–17 years) divided into intervention and control groups. The intervention consisted of 12 weeks of periodic resistance training (3×/week), while the control group continued with conventional training. Performance variables were measured using VO_2max, 30 m sprints, vertical jumps, and the T-test for agility, while injuries were tracked using the FIFA surveillance system. Paired t-test and independent t-test analyses showed significant improvements (p < 0.05) across all performance variables in the intervention group, alongside a 32% reduction in injury rates. These results conclude that quality-based resistance training contributes significantly to performance enhancement and injury prevention in youth soccer athletes.